2017
DOI: 10.1002/adma.201606321
|View full text |Cite
|
Sign up to set email alerts
|

Silicon/Organic Hybrid Solar Cells with 16.2% Efficiency and Improved Stability by Formation of Conformal Heterojunction Coating and Moisture‐Resistant Capping Layer

Abstract: Silicon/poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) heterojunction solar cells with 16.2% efficiency and excellent stability are fabricated on pyramid-textured silicon substrates by applying a water-insoluble ester as capping layer. This shows that a conformal coating of PEDOT:PSS on textured silicon can greatly improve the junction quality with the main stability failure routes related to the moisture-induced poly(3,4-ethylenedioxythiophene) aggregations and the tunneling silicon oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
123
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 32 publications
(29 reference statements)
1
123
0
1
Order By: Relevance
“…[28][29][30][31][32] Metal-oxide, fluoride, and polymerbased DF-CSCs are easy to deposit at an acceptable cost (e.g., thermal evaporation, spin coating, or atomic layer deposition, ALD); however, most of them suffer from a poor stability, either chemically or thermally, [11,16,18,23,24,33] which limits their industrial applications. When the metal is in direct contact with the silicon surfaces, very large densities of electronic states at the interface can be introduced into 8-hydroxyquinolinolato-lithium (Liq), perylene diimide, have also been developed.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32] Metal-oxide, fluoride, and polymerbased DF-CSCs are easy to deposit at an acceptable cost (e.g., thermal evaporation, spin coating, or atomic layer deposition, ALD); however, most of them suffer from a poor stability, either chemically or thermally, [11,16,18,23,24,33] which limits their industrial applications. When the metal is in direct contact with the silicon surfaces, very large densities of electronic states at the interface can be introduced into 8-hydroxyquinolinolato-lithium (Liq), perylene diimide, have also been developed.…”
Section: Introductionmentioning
confidence: 99%
“…These issues have motivated studies to search for alternative new functional materials and simplified deposition technologies, whereby we can directly form high quality of heterojunctions with c‐Si substrates in a dopant‐free manner. During the past 5 years, dopant‐free HSCs with hole‐selective transport materials (e.g., molybdenum oxide (MoO x ), tungsten oxide (WO x ), vanadium oxide (V 2 O x ), and poly(3,4‐ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT:PSS)) and electron‐selective transport materials (e.g., titanium dioxide (TiO 2 ), magnesium oxide (MgO x ), and magnesium fluoride (MgF x )) have already been implemented on c‐Si absorbers and promising progress has been achieved.…”
mentioning
confidence: 99%
“…Recently, it has been reported that the conductivity of PEDOT:PSS films can be increased about three orders of magnitude by addition of solvents, such as dimethyl sulfoxide (DMSO), ethylene glycol, or 2‐methylimidazole . Meanwhile, recent studies have also revealed that the improved uniformity of the PEDOT:PSS film deposited on the Si substrate has been enabled by adding surfactants (FS300 and Triton X‐100) in PEDOT:PSS solution, both of which have resulted in the improved device performance of organic/n‐Si planar heterojunction solar cells. Although numerous works have confirmed modifying the PEDOT:PSS film capable of enhancing the efficiency for PEDOT:PSS/n‐Si heterojunction solar cells, it is not clear what the dominant origin for the improvement of conductivity of PEDPT:PSS film is .…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous works have confirmed modifying the PEDOT:PSS film capable of enhancing the efficiency for PEDOT:PSS/n‐Si heterojunction solar cells, it is not clear what the dominant origin for the improvement of conductivity of PEDPT:PSS film is . The working mechanism of the heterojunction and the relationship between the material properties of the PEDOT:PSS layer and the device performances are poorly understood, and it is not clear what the dominant origin for enhanced device performance based on the PEDOT:PSS interlayer is . The J SC and FF of PEDOT:PSS/n‐Si heterojunction solar cell are lower when compared with the conventional homogeneous p–n Si junction solar cell .…”
Section: Introductionmentioning
confidence: 99%